Effect of cimetidine and pirenzepine in combination on 24 hour intragastric acidity in subjects with previous duodenal ulceration. Issue 4 (April 1986) - Williams, J G; Deakin, M; Ramage, J K
Abstract : Intragastric pH was monitored during 24 hours in eight volunteers with duodenal ulcer disease in remission, while on placebo, cimetidine 400 mg bd, pirenzepine 50 mg bd, cimetidine 400 mg bd + pirenzepine 50 mg bd, cimetidine 200 mg bd + pirenzepine 25 mg bd. The control of intragastric acidity during the 24 hour period by the combination of low dose cimetidine and pirenzepine was significantly better than with cimetidine, or pirenzepine alone in full dosage. This difference was most apparent after breakfast but was still present after lunch when cimetidine had no significant effect. Combination treatment is a logical approach when continuous control of intragastric acidity is needed, but a three times daily regimen will be necessary to cover the 24 hours.